Nigeria - Country Assistance Evaluation - World Bank (Washington, DC, 2012)
The period from July 1, 1998 to June 30, 2007 (World Bank fiscal years 99-07) saw a substantial improvement in Nigeria's economic performance and outlook relative to the previous two decades, during which, notwithstanding the expanding production of oil and gas, Nigeria's social indicators deteriorated steadily and the country acquired among the worst reputations for corruption and poor governance. During its second term, the Obasanjo administration built on some actions taken previously to stabilize the economy, created an oil surplus account to prevent the fiscal instability of the earlier period, took significant steps to improve public financial management, put in place important new initiatives on corruption and transparency, and continued the privatization program. During this period, the Bank provided important assistance to the government of Nigeria. In spite of the relatively small weight of the Bank's financial contribution given Nigeria's earnings from oil, the Bank carried a great deal of weight as a source of objective advice and as a means of influencing perceptions of Nigeria in the international community. During the period to mid-2003, however, the Bank had some difficulty in determining the role it should play. A large number of lending operations were started, often without the base of local knowledge needed for success. At the same time, the Bank was slow to invest in analytic work. With the reform team providing clear Nigerian leadership in the second term of President Obasanjo, the Bank adapted its program in many areas to provide effective support. The Bank is well placed to continue to make an important contribution to Nigeria's economic and social progress. For this to occur, it is important that the Nigerian government take all necessary steps to ensure policy continuity as well as to extend and deepen the reforms initiated over the evaluation period-this is of critical importance for the country's long-term economic success.